(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Communication is the lifeline of every organization. A communication audit is an idea, a concept, tool or instrument used to diagnose strengths and weaknesses of the communication system of the organization. Corporate communications are the communication functions of an organization, actively involved in the decision-making process, and forming a strategy for handling internal and external communications. The following paper studies three objectives, first to understand the relevance of adoption of communication audit, second to analyze the reasons for adoption and rejection of communication audit, and lastly, to find out the adaptation of communication audit in corporate communications. Corporate communication managers were interviewed and the data was analyzed based on the adoption theory of Everett Rogers’s Theory of Diffusion of Innovation. By analyzing the persuasive and decision making factors for adopting a communication audit, and finding out a list of adapted tools used in the department, there is a clear indication of the need for adoption of communication audit in the corporate communication department. Also, looking at the other ways used for analyzing communication, an adaptation of communication audits in some form has also been seen in the corporate communications of organizations.